GENDER STEREOTYPES IN ENOLA HOLMES: A FILM ANALYSIS OF THE MAIN CHARACTER - Azis, Nurul Rusyaidah; Sunra, La (ELITERATE : Journal of English Linguistics and Literature Studies, 2022)
This research is about the film Enola Holmes. This study aims to determine the types of gender stereotypes depicted by the main character, Enola Holmes, based on the conversations and actions he performs. This study also aims to determine the effect of gender stereotypes on Enola Holmes in the film Enola Holmes. This research is descriptive qualitative research with research methods. The data in this study were taken from the transcript of the film Enola Holmes. Data analysis was carried out using interactive model analysis which included data reduction, data mapping, and drawing conclusions (Miles & Huberman & Saldana, 2014). The results of this study indicate that there are 2 types of gender stereotypes described by Enola Holmes in the film Enola Holmes, namely femininity and masculinity. In addition, the results of the study also found the effect of gender stereotypes on Enola Holmes, namely the effect of femininity and the effect of masculinity.